Digital Three-Dimensional Atlas of Quail Development Using High-Resolution MRI - Seth W. Ruffins; Melanie Martin; Lindsey Keough; Salina Truong; Scott E. Fraser; Russell E. Jacobs; Rusty Lansford (The Scientific World Journal)
We present an archetypal set of three-dimensional digital atlases of the quail embryo based on microscopic magnetic resonance imaging (μMRI). The atlases are composed of three modules: (1) images of fixed ex ovo quail, ranging in age from embryonic day 5 to 10 (e05 to e10); (2) a coarsely delineated anatomical atlas of the μMRI data; and (3) an organ system-based hierarchical graph linked to the anatomical delineations. The atlas is designed to be accessed using SHIVA, a free Java application. The atlas is extensible and can contain other types of information including anatomical, physiological, and functional descriptors. It can also be linked to online resources and references. This digital atlas provides a framework to place various data types, such as gene expression and cell migration data, within the normal three-dimensional anatomy of the developing quail embryo. This provides a method for the analysis and examination of the spatial relationships among the different types of information within the context of the entire embryo.